Running to Stand Still? - Intellectual Property and Value Added in Innovating Firms. - Greenhalgh, C; Longland, M (Department of Economics (University of Oxford), 2002)
We construct a unique panel dataset to examine how R&D; and intellectual property (IP), via patents and trade marks, increase firm productivity. Knowledge has public good characteristics of non-depletability and non-excludability. Even with IP, imitation and inventing around other firm's products is possible, so we examine the size and duration of benefits to IP protection. If non-depletion is correct, this implies that absolute R&D;, or total IP assets are important. We examine this hypothesis against the alternative of depletability, where innovative intensity relative to the size of the firm matters. The results support rapid depletability and poor ability to exclude.